Scooby-Doo! Pirates ahoy!. - Kasem, Casey; Welker, Frank; Cohn, Mindy, 1966-; DeLisle, Grey.; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2006)
It's high-seas hilarity when Scooby-Doo and the gang take a creepy cruise into the legendary Bermuda Triangle! Spooks and scares lurk around every corner - from alien sightings to terrifying Skeleton Ghost Pirates that sink cruise ships with cannonballs.
Title from container.
Voices: Casey Kasem, Frank Welker, Mindy Cohn, Grey DeLisle.
Not rated.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital, DVD-5, single-sided.
Closed captioned for the hearing impaired.
Can be viewed subtitled in English, French or Spanish.
Keywords: Scooby-Doo -- (Fictitious character) -- Drama; Private investigators -- Drama; Criminal behavior -- Bermuda Triangle -- Drama; Feature films; Animated films; Comedy films; Children's films; Films for the hearing impaired; Comedy -- Animation -- Feature; Children's -- Animation -- Feature; Animal -- Animation -- Feature; Animated films; Comedy films; Children's films